Comparison of efficacy of caries removal using polymer bur and chemomechanical caries removal agent: A clinical and microbiological assessment - An in vivo study - K Krishna Aswathi; S Prathibha Rani; Anantharaj Athimuthu; Praveen Prasanna; Prasannakumari Patil; K J Deepali (Wolters Kluwer Medknow Publications, 2017)
Background and Objectives: Conservative caries removal has become an integral part of minimally invasive dentistry (MID). Polymer burs and chemomechanical caries removal are two feasible methods of MID. The objective of this study was to assess and compare the efficacy of polymer bur and chemomechanical caries removal agent clinically and microbiologically for selective removal of infected dentin. Methods: A total of fifty primary second molars with occlusal decay involving dentin were selected from 25 patients aged between 5 and 9 years. They were randomly allocated to Group A (polymer bur group) and Group B (Carie-Care group) for caries removal. Completeness of caries excavation was assessed clinically with the application of caries detector dye. Dentinal samples were collected before and after caries removal and cultured in Luria-Bertani Agar, and total viable count was assessed. All the teeth after caries excavation were restored with Type 2 glass ionomer cement. The data obtained was tabulated and statistically analyzed using paired t-test and Chi-square test. Results: There was a statistically significant reduction in the mean microbial count before and after treatment in polymer bur group and Carie-Care group. The reduction in mean microbial count was found significantly higher in polymer bur group compared to Carie-Care group. There was no significant association was observed between the two groups when efficacy was assessed clinically. Conclusions: Both polymer bur and Carie-Care were efficient caries removal agents when assessed clinically and microbiologically. Polymer bur was found to be more effective than Carie-Care when assessed microbiologically.